2022
DOI: 10.2174/1568009622666211231140623
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Natural Products in the Treatment of Triple-negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer that lacks receptors for targeted therapy. Consequently, chemotherapy is currently the mainstay of systemic treatment options. However, the enrichment of cancer stem cells (CSC, a subpopulation with stem-cell characteristics and tumor-initiating propensity) promotes chemo-resistance and tumorigenesis, resulting in cancer recurrence and relapse. Furthermore, toxic side effects of chemotherapeutics reduce patient wellbeing. Natural products, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 183 publications
0
17
0
Order By: Relevance
“…Several mechanisms have been implicated in the inhibition of cell proliferation: (i) inhibition of the activity of tyrosine-specific protein kinases [ 126 , 127 , 128 ], such as inhibition of PKC, which is one of the key enzymes in the regulation of cellular proliferation and tumor growth; (ii) induction of the differentiation of carcinoma cells [ 3 , 13 , 126 , 127 , 128 , 129 ]; (iii) transcriptional changes in cell cycle- and apoptosis-related genes such as NF-κB, Bcl-X(L) and COX-2; (iv) binding to the estrogen receptor and inhibition of an estrogen receptor-positive human breast cancer cells [ 130 , 131 ]; (v) induction of apoptosis, (vi) downregulation of the expression of mutated H-Ras and p53 tumor suppression gene [ 3 , 13 , 126 ], (vii) modulation of gene methylation and re-expression of tumor suppressors or other genes silenced by aberrant DNA methylation [ 119 , 130 , 131 ], (viii) inhibition of pro-oxidative enzymes xanthine oxidase, cyclooxygenases, or lipooxygenases [ 3 , 13 , 126 , 127 ], and (ix) some flavonoids are a direct poison for topoisomerase II (TopoII), through the stabilization of double strand breaks in the TopoII-DNA cleavage [ 4 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…Several mechanisms have been implicated in the inhibition of cell proliferation: (i) inhibition of the activity of tyrosine-specific protein kinases [ 126 , 127 , 128 ], such as inhibition of PKC, which is one of the key enzymes in the regulation of cellular proliferation and tumor growth; (ii) induction of the differentiation of carcinoma cells [ 3 , 13 , 126 , 127 , 128 , 129 ]; (iii) transcriptional changes in cell cycle- and apoptosis-related genes such as NF-κB, Bcl-X(L) and COX-2; (iv) binding to the estrogen receptor and inhibition of an estrogen receptor-positive human breast cancer cells [ 130 , 131 ]; (v) induction of apoptosis, (vi) downregulation of the expression of mutated H-Ras and p53 tumor suppression gene [ 3 , 13 , 126 ], (vii) modulation of gene methylation and re-expression of tumor suppressors or other genes silenced by aberrant DNA methylation [ 119 , 130 , 131 ], (viii) inhibition of pro-oxidative enzymes xanthine oxidase, cyclooxygenases, or lipooxygenases [ 3 , 13 , 126 , 127 ], and (ix) some flavonoids are a direct poison for topoisomerase II (TopoII), through the stabilization of double strand breaks in the TopoII-DNA cleavage [ 4 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…The combination of natural products with other drugs also has great potential to improve the treatment efficacy of TNBC. [18][19][20] Diindolyl methane (DIM) derivatives are one such naturally derived pharmacophore which have reported anticancer action in various cancer cells. Here, we have subjected a total of 12 synthetic biaryls appended DIM derivatives for cytotoxicity testing against the TNBC cell line MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…34 PI3K/Akt/mTOR pathway is an intracellular signalling pathway involved in cell growth/tumour proliferation, and multiple inhibitors targeting this pathway are already in clinical trials. [35][36][37] It can be regulated from the cellular recognition site or at the miRNA level. 38 I3C, DIM and their derivatives have pleiotropic antitumour effects with multiple biological targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, Buhrmann and colleagues have shown that curcumin had the potential to dramatically decrease the crosstalk between CSCs and stromal fibroblasts (Buhrmann et al, 2014) (Figure 4). Additionally, an important aspect of its pharmacological effects relies on inhibition of several pathways important for CSCs, such as NF-κB, PI3K/Akt/mTOR, Notch, Wnt, and Hippo/YAP (Ke et al, 2021), but also of signaling crosstalks involved in chemoresistance (Vinod et al, 2013). Moreover, unlike other Hedgehog inhibitors that produced some adverse effects in vivo, the combination of curcumin with chemotherapeutics or targeted agents has represented a new therapeutic strategy with low or no toxicity (Li et al, 2012;.…”
Section: Molecular and Cellular Cancer Emt: Targets Of Curcuminoidsmentioning
confidence: 99%